2021
DOI: 10.1186/s40337-021-00440-6
|View full text |Cite
|
Sign up to set email alerts
|

“Putting your own oxygen mask on first”: a qualitative study of siblings of adults with anorexia or bulimia

Abstract: Background In families where one of the siblings has an eating disorder (ED), research indicates that the siblings without eating disorders (EDs) experience insufficient care and negative changes in family life. The illness then takes up a great deal of space within the family. Support from the siblings without EDs is considered to be important for the recovery of the sibling with ED. A key issue is how to involve siblings without EDs in treatment and establish what kind of support they themsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…A third study [32] reported how healthy sisters (n = 21) of women with ED may also evince more difficulties and avoidance in the recognition of their own emotions as compared to non-related controls, through both self-report and experimental task based on picture of faces. Further recent studies proposed additional qualitative reports of distress in this population [33,34].…”
Section: Psychological Mechanismsmentioning
confidence: 86%
“…A third study [32] reported how healthy sisters (n = 21) of women with ED may also evince more difficulties and avoidance in the recognition of their own emotions as compared to non-related controls, through both self-report and experimental task based on picture of faces. Further recent studies proposed additional qualitative reports of distress in this population [33,34].…”
Section: Psychological Mechanismsmentioning
confidence: 86%
“…She has conducted two years of fieldwork with MFT for adults with EDs and has published two articles based on this work [2,3]. She has also supervised master's students [27] and a PhD student [28,29] on studies about EDs. Although she has not worked clinically with persons with EDs, she has expertise in ethics and her thinking is inspired by the Danish philosopher and theologian K.E.…”
Section: Beritmentioning
confidence: 99%
“…Research shows that EDs greatly affect parents, siblings and the wider family [25][26][27][28][29] and are experienced as more demanding for the family than, for example, psychotic disorders [30][31][32]. Furthermore, studies show that those closest to a family member with an ED suffer from isolation and receive little help from support services [27][28][29][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…The combined difficulties of changing family roles, coupled with feelings of fear, guilt and sadness about their sibling's illness [16,[46][47][48], make this experience very distressing. Additionally, well siblings may struggle to discuss their feelings due to a reduced availability of family members and a desire not to burden them further [49,50]. These difficulties are discussed in the model as social and emotional maintaining factors.…”
Section: Introductionmentioning
confidence: 99%